2016
DOI: 10.1016/j.biombioe.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts of power generation from residual biomass

Abstract: The European Union relies largely on bioenergy to achieve its climate and energy targets for 2020 and beyond. We assess, using Attributional Life Cycle Assessment (A-LCA), the climate change mitigation potential of three bioenergy power plants fuelled by residual biomass compared to a fossil system based on the European power generation mix. We study forest residues, cereal straws and cattle slurry. Our A-LCA methodology includes: i) supply chains and biogenic-CO2 flows; ii) explicit treatment of time of emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 46 publications
1
37
0
4
Order By: Relevance
“…The absolute global surface temperature change potential (AGTP) can directly reflect the impact of a certain greenhouse gas emission from the perspective of surface temperature rise [48,49]. The gas emissions (kg) over the time period multiplied by the corresponding warming potential AGTP (K•kg −1 ) can estimate the surface temperature response variations (∆T) [49][50][51]. In this paper, ∆T indicates the warming potential caused by the accumulation of CH 4 emissions during a 15-year time period.…”
Section: Surface Temperature Responsementioning
confidence: 99%
“…The absolute global surface temperature change potential (AGTP) can directly reflect the impact of a certain greenhouse gas emission from the perspective of surface temperature rise [48,49]. The gas emissions (kg) over the time period multiplied by the corresponding warming potential AGTP (K•kg −1 ) can estimate the surface temperature response variations (∆T) [49][50][51]. In this paper, ∆T indicates the warming potential caused by the accumulation of CH 4 emissions during a 15-year time period.…”
Section: Surface Temperature Responsementioning
confidence: 99%
“…On the other hand, only two studies (Negro et al 2017;Li et al 2018) selected a mass unit as the functional unit. In addition, 4 out of the 16 studies explicitly stated the use of attributional ELCA (Boulamanti et al 2013;Agostini et al 2015;Giuntoli et al 2015Giuntoli et al , 2016 but all 16 studies conducted the ELCA in a consequential manner. The authors decided to modify the waste management practice of the original system, modelling an alternative end-use of the investigated waste feedstock.…”
Section: Methodsmentioning
confidence: 99%
“…The most recent EU RED policies declare biofuel to be carbon neutral regardless of the source of biofuel (Schiermeier 2018); therefore, energy generating facilities may claim zero emissions even though the fuel producing country incurs an emissions debit in the land sector. However, numerous studies of increasing bioenergy use have revealed that depending on feedstock, changes in the forest supplying the feedstock can have significant impacts on the overall net emissions of GHGs and therefore need to be considered as a significant part of the complete carbon footprint (Agostini et al 2013, Giuntoli et al 2016, Guest et al 2013.…”
Section: Introductionmentioning
confidence: 99%